Efficient Bioreduction of Cyclohexyl Phenyl Ketone by Leuconostoc Pseudomesenteroides N13 Biocatalyst Using a Distance-Based Design-Focused Optimization Model - Ozdemir, Akin; Sahin, Engin (Elsevier, 2022)
Whole-cell biocatalysts have been a popular method for the preparation of chiral alcohols. Although asymmetric reduction of cyclohexyl(phenyl)methanone (1) by chemical catalysts is common, a biocatalytic asymmetric reduction is extremely rare. In this respect, we report herein that Leuconostoc pseudomesenteroides N13 was successfully employed as a biocatalyst to reduce 1 to (S)-cyclohexyl(phenyl)methanol ((S)-2). Furthermore, the use of a mathematical optimization strategy for asymmetric reduction of substrate 1 is not known in the current literature. The new distance-based design-focused optimization model was used to enhance the conversion of the substrate, enantiomeric excess (ee) of product, and yield. The distance-based design-focused optimization model identified the following optimal bioreduction conditions: pH=6.46, temperature=30 degrees C, incubation period=72 hours, and agitation speed=199 rpm. Then it was stated that under these ideal conditions, (S)-2 may be produced with 99 % ee and 98.46 % conversion rate (cr). (S)-2 was achieved with 99% ee, and 99% cr as a consequence of the experimental reaction carried out under the indicated optimization conditions. It has been shown that Leuconostoc pseudomesenteroides N13 can be utilized as a biocatalyst in asymmetric reduction reactions. This study, in addition to being the first example of a bioreduction of substrate 1 by mathematical optimization, also demonstrates for the first time the distance-based design-focused model can be used in the bioreduction reaction.
Keywords: Distance-Based Design Method; Biocatalyst; Asymmetric Reduction; Chiral Secondary Alcohol; Drug Precursor